Comparative Analysis of Soil-Water Characteristic Curve in Fractal and Empirical Models. (5th June 2020) - Tao, Gaoliang; Chen, Yangyang; Xiao, Henglin; Chen, Yin; Peng, Wan
Abstract : The fitting analysis of soil-water characteristic curve (SWCC) is the foundation of engineering properties of unsaturated soils. The purpose of this paper is to explore the differences of fitting effects between different fractal and empirical models as well as the effect of residual water content θ r on the model fitting. The experimental SWCCs of Hunan clay at different initial dry densities are measured by pressure plate instrument, and then they are fitted by fractal and empirical models. The effect of the limit of θ r on the fitting results is analyzed by comparing the results of indoor evaporation test. The results show that within the measured data point range, fractal model II-2 and van Genuchten model (VG model) have the best fitting effect, fractal models I and II-1 take the second place, and the fitting effect of Gardner model is the worst. When the matrix suction is more than the measured data, the fitting accuracy of the model is poor. For the model with θ r, reasonable limit range of θ r can only improve the fitting accuracy of the model to a certain extent. For the fractal model, the fitting accuracy of the model can be improved effectively when θ r is considered. Furthermore, the difference of fractal dimension and air-entry value in various fractal models are also discussed in this paper.